How Class Difference Affects The Thinking of The South in Relation to Racial Supremacy - Sakvithi, D. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
The long polarized Sri Lankan civil war has been viewed by Southern Sinhalese community in related to their social class that is different in levels of wealth, education and social status. This research is based on how changes in politics and education dynamically affect the idea of racial supremacy. When the society increases in knowledge communities become capable of seeing each other’s point of view. However, in some cases, the ability to see the other’s point of view is much more politically biased due to a lack of education. The lower middle class who lacks university level education or rather, even with university education, lacks enough income to sustain the family properly, tends to believe in racial supremacy. The reverse is true when it comes to the upper middle class where the community is much more liberal and freer from ideas of racial supremacy with certain exceptional cases, which is primarily a consequence of education. Furthermore, political changes in some cases, influence the lower middle class as well, where they tend to navigate through liberal ideas related to racism with their political ideology. The laws regarding education reforms may change the story where sustainable implementation of new laws and expectations are discussed herewith. The laws of education have long term effects toward politics where equality will be identified by all the communities. Moreover, such grassroots view changes might have long term effects such as the overall Southern community may see other’s point of view. However, the Southern community who are below the class level of upper middle class might influence from political changes happen time to time even if the progress of liberal view grows steadily. What is more, the Southern lower classes have same rituals in relation to their poverty born consequences as Northern lower classes have. Education is the key to both communities in South and North to understand what is in the other end where both will be able to come to a consensus and be compassionate to the other side.
Keywords: Lower middle class; Upper middle class; Political bias; Racial supremacy; Poverty